Fatwa dalam perundangan Islam dan fungsinya menangani keperluan hukum semasa menurut siasah al-Syar’iyah - Hasnan Kassan,; Jasri Jamal, (Fakulti Undang - Undang, 2003)

(untitled)
Islamic laws is practicable since the period of Muhammad (s.a.w.) until the Days of Here After. The gist of its teachings covers whole aspects of human life, fits alt human activities at any time and places. As a result to the expansion and changes in human life, however, Muslims face unsolved problems due to vagueness of Hukum Syarak. This situation generates the need for fatwa Mufti to come out with concessus of hukum. With respect to the subject, this working paper will discuss on the concept of fatwa in Islamic laws and its significance according to siasah syar’iyyah